DOP60 The interleukin 22 transcriptional programme is activated in human colonic inflammation and associated to anti-TNFα primary non-response in Crohn's. (25th January 2019) - Pavlidis, P; Tsakmaki, A; Niazi, U; Digby-Bell, J; Lombardi, G; Hayee, B; Bewick, G; Powell, N
Abstract: Background: Interleukin 22 (IL-22) is an effector cytokine regulated by IL-23, a key player in IBD pathogenesis and target of novel biologics. Preclinical studies suggest a protective role for IL-22 in the context of acute intestinal injury and an inflammatory one in chronic inflammation. Little is known though about its role in human IBD. Methods: Considering that the only tissue responsive to IL-22 is the intestinal epithelium, we generated colonic organoids (colonoids) from biopsies taken from healthy controls ( n = 4) and treated them with IL-22, or other cytokines relevant to IBD pathogenesis (TNFα, IL-17A, and IFNγ). Whole transcriptome profiling was performed using the Illumina platform. Association to clinical phenotypes was performed with gene set variation analysis (GSVA) by testing for enrichment of the generated IL-22 transcriptional signature (top 50 up-regulated transcripts) in our own (controls: 6; UC: 16) and reposited datasets (GSE59071 and GSE16879). Results: The IL-22 transcriptional programme was the second largest based on number of differentially expressed genes (DEG) induced in human colonoids by IBD-relevant cytokines (IL-22: 1251, IFNγ: 1310, TNFα: 716, IL17A: 245, filtering on FDR < 0.01). Most of the transcripts regulated by IL-22 were shared with the other transcriptional programmes (79% of DEG) while in hierarchical clustering IL-22 clustered closely to TNFα and IL17A. Among the most highly enriched GO terms for all four cytokines were 'cytokine-mediated signalling pathway', 'cytokine production', 'response to wounding', 'regulation of cell adhesion' with concordant activation across conditions (up-regulation). All transcriptional signatures, including IL-22, were enriched in active inflammation regardless of phenotype (UC, colonic CD). Enrichment for the IL-22 and TNFα transcriptional profiles prior to starting anti-TNFα therapy was associated with primary non-response in CD (area under the ROC curve: 0.88, p = 0.007 and 0.87, p = 0.009) but not UC. Conclusions: We identify, for the first time, striking transcriptional similarities between IL-22 and other pro-inflammatory cytokines known to drive IBD. We show that the IL-22 regulated transcriptional programme is active in the context of human colonic inflammation and, importantly, enriched in those CD patients who failed anti-TNFα induction. Our findings highlight the therapeutic potential of IL-22 targeted personalised medicine approaches for human intestinal inflammation.